2014
DOI: 10.1096/fj.14-259614
|View full text |Cite
|
Sign up to set email alerts
|

Essential nutrient supplementation prevents heritable metabolic disease in multigenerational intrauterine growth‐restricted rats

Abstract: Intrauterine growth restriction (IUGR) confers heritable alterations in DNA methylation, rendering risk of adult metabolic syndrome (MetS). Because CpG methylation is coupled to intake of essential nutrients along the one-carbon pathway, we reasoned that essential nutrient supplementation (ENS) may abrogate IUGRconferred multigenerational MetS. Pregnant SpragueDawley rats underwent bilateral uterine artery ligation causing IUGR in F1. Among the F2 generation, IUGR lineage rats were underweight at birth (6.7 vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 83 publications
(140 reference statements)
8
38
0
Order By: Relevance
“…In rats, uterine ligation leads to development of the metabolic syndrome in the offspring including type 2 diabetes, dyslipidemia, and hypertriglyceridemia [45][46][47]. Interestingly, many of these symptoms were reciprocated into the F2 generation [48]. These metabolic deficits exist, in part, due to altered glucose transporter expression, impairment of fatty acid metabolism, increased glucocorticoid activity, augmented glucose production, and blunted insulin suppression all within the liver [45,47,[49][50][51].…”
Section: Uterine Ligation or Ablation Model Of Undernutrition And Lonmentioning
confidence: 99%
See 3 more Smart Citations
“…In rats, uterine ligation leads to development of the metabolic syndrome in the offspring including type 2 diabetes, dyslipidemia, and hypertriglyceridemia [45][46][47]. Interestingly, many of these symptoms were reciprocated into the F2 generation [48]. These metabolic deficits exist, in part, due to altered glucose transporter expression, impairment of fatty acid metabolism, increased glucocorticoid activity, augmented glucose production, and blunted insulin suppression all within the liver [45,47,[49][50][51].…”
Section: Uterine Ligation or Ablation Model Of Undernutrition And Lonmentioning
confidence: 99%
“…Elegant studies in the baboon fetus have demonstrated that 70% undernutrition during pregnancy led to augmented hepatic gluconeogenesis associated with both increased Pck1 mRNA and decreases in the methylation of CpG dinucleotides of the Pck1 promoter [59]. Moreover, uterine ligation has been shown to directly increase DNA methylation in the promoter of hepatic Igf-1 at birth and that this persists into the F2 generation even when F1 IUGR offspring are adequately nourished [48,74]. Interestingly, in this study, supplementation of the diet in the F1 IUGR offspring with folic acid, choline, betaine, vitamin B 12 , and other essential nutrients prevented the methylation of the Igf-1 promoter in the F2 generation along with symptoms of the metabolic syndrome [48].…”
Section: Direct Mechanisms Linking Maternal Undernutrition and Adversmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that in men, early childhood may represent a particularly sensitive period for the development of atherosclerosis. Although these studies were not designed to capture the underlying mechanisms of these “bad memories,” it is plausible that epigenetic changes imparting maladaptive signatures in adipocytes or other metabolic tissues may contribute to these findings 7-10 . What about the reports in ATVB on the consequences of obesity in human subjects?…”
Section: Tracking Obesity and Its Consequences From Birth To Adulthoomentioning
confidence: 99%